If Supply-Oriented Drug Policy is Broken, Can Harm Reduction Help Fix It?—Melding Disciplines and Methods to Advance International Drug Control Policy - Letizia Paoli
Critics of the international drug control regime contend that supply-oriented policy interventions are not just ineffective, but they also produce unintended adverse consequences. Research suggests their claims have merit. Lasting local reductions in opium production are possible, albeit rare; but, unless global demand shrinks, production will shift elsewhere, with little or no effect on the aggregate supply of heroin and, potentially, at some expense to exiting and newly emerging suppliers. The net consequences of the international drug control regime and related national policies are as yet unknown. In this paper, we consider whether “harm reduction,” a subject of intense debate in the demand-oriented drug policy community, can provide a unifying foundation for supply-oriented drug policy, one capable of speaking more directly to policy goals. Despite substantial conceptual and technical challenges, we find that harm reduction can provide a basis for assessing the net consequences of supply-oriented drug policy, choosing more rigorously among policy options, and identifying new policy options. In addition, we outline a practical path forward for assessing harms and policy options.